Unrecorded species of Korean invertebrates discovered through the project of 'Discovery of Korean Indigenous Species' II. - Ji, S.J., J.W. Joo, S.H. Kim, D.H. Ahn, M.S. Kim, J.H.Lee, H.M.Yang, G.H. Lee, E.J.Nam, T.S. Park, A.B. Jöst, H.M. Pham, J. Park, J.H. Park, .Y.Keum, I. Karanovic, T. Karanovic, J.K.Park, C.L. Jung & G.S. Min (Journal of Species Research, 2023)
This is the third series of catalogs reporting on Korean species discovered through the ‘Discovery of Korean Indigenous Species’. This catalog includes 22 species of invertebrates, excluding insects. The catalog includes the scientific name, an abridged list of synonyms, collection sites, distribution, diagnosis, and figures for each species. Additionally, we provide the newly assigned Korean name, specimen voucher, and, if available, mitochondrial CO1 or 16S gene sequences of the species listed. All species identified and documented here will be officially listed on the ‘National Species List of Korea’, a database maintained by the National Institute of Biological Resources (NIBR).